2020
DOI: 10.1002/hpm.3034
|View full text |Cite
|
Sign up to set email alerts
|

How investment in public health has impacted the prevalence of tuberculosis in China: A study of provincial variations between 2005 and 2015

Abstract: How do public investments in public health actually impact health outcomes? This question has not been investigated enough, especially regarding infectious diseases. This study investigates the correlations between public health expenditure and the incidence of tuberculosis in China using a provincial panel dataset. The analysis focuses on the correlations between public health expenditure and tuberculosis incidence, using the fixed effects models and Two Stage Least Squares (2SLS) method. Overall, a 10% incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Second, per capita health expenditure has a negative impact on the reported incidence. This is similar to other research [ 35 , 36 ]. Health expenditure is mainly used for public health and the improvement of the health of the local population, including the costs of TB treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Second, per capita health expenditure has a negative impact on the reported incidence. This is similar to other research [ 35 , 36 ]. Health expenditure is mainly used for public health and the improvement of the health of the local population, including the costs of TB treatment.…”
Section: Discussionsupporting
confidence: 93%
“…This result was also consistent with Hypothesis 1 and was expected for the same reasons stated above in terms of HIV/AIDS care. Moreover, this result was consistent with the conclusions of several previous studies, which indicated that PHS played an important role in TB reduction (Bergonzoli et al, 2016;Liu et al, 2020;Wagstaff & Cleason, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Medical resources ( ): Local fiscal health expenditure per capita is an important indicator to measure the accessibility of medical and health resources in a region. The higher the local financial health expenditure per capita, the more abundant medical resources and the better the medical and sanitary conditions in an area, and the lower the morbidity of respiratory infectious diseases [ 38 ]. We collected the per capita local financial health expenditure from the China Statistical Yearbook to control the impact of medical resources.…”
Section: Datamentioning
confidence: 99%